Molecular orbital analysis of the reaction paths for termolecular reactions - Ibrahim Ali , Noorbatcha (National Institute of Science Communication and Information Resources, 1999)
The possibility of a six centered transition state for the termolecular exchange reaction between three diatomic molecules (A(2) + B-2 + C-2 --> AB + BC + CA) is investigated using Extended Huckel Theory. Our present calculations show that a concerted six-centered reaction mechanism is energetically more favourable compared to the atomic mechanism for these type of reactions. An analysis of the molecular orbitals of the transition state shows that the six sigma electrons, originating from the each atom, are completely delocalized throughout the cyclic six-membered transition state. This effect is analogous to the delocalization observed in conjugated cyclic systems containing (4n+2) pi electrons. The concept of sigma aromaticity arising from the delocalization of sigma electrons in cyclic transition states can be successfully applied to explain the mechanism of termolecular reactions.